Integrating stimulus-based concept/mind mapping into interactive biology 'cheat sheets' - Meera Rada Krishnan, * (Sunway University College, 2010)
This approach of teaching centres on the construction of structured graphic displays of conceptual schemes within well circumscribed domains. It introduces students to the complete visualisation of any topic based on the key concepts acting as a stimulus. Every topic review begins with brainstorming to recognise and identify all key concepts, followed by a hierarchical organisation of related clusters of concepts. Each stimulus creatively initiates a chain reaction, consecutively linking to relevant subtopics which in turn are mind-mapped to all other detailed supporting data. It breaks down otherwise overwhelming amounts and depths of data into simple key concepts without compromising on subject coverage. This leads to the much needed flexibility for students to get familiarised with integrating their own ideas into effectively planning and organising a complete and compact ?cheat sheet?. Students develop the skill to retain and reproduce all relevant information on a topic sparked off by the stimulus. Furthermore, students enthusiastically look forward to the lessons due to this diverse and attention grabbing technique. This method effectively encourages students to be more proactive as well as guides students to quickly grasp the overview of any topic and focus on relating the relevant concepts to the key concepts for long term understanding. It is a skill that cultivates into a habitual attribute that is applicable at all academic levels.